Absolute Lymphocyte Count Is Not a Suitable Alternative to CD4 Count for Determining Initiation of Antiretroviral Therapy in Fiji - Dashika A. Balak; Karen Bissell; Christine Roseveare; Sharan Ram; Rachel R. Devi; Stephen M. Graham (Journal of Tropical Medicine)
Introduction. An absolute lymphocyte count is commonly used as an alternative to a CD4 count to determine initiation of antiretroviral therapy for HIV-infected individuals in Fiji when a CD4 count is unavailable. Methods. We conducted a retrospective analysis of laboratory results of HIV-infected individuals registered at all HIV clinics in Fiji. Results. Paired absolute lymphocyte and CD4 counts were available for 101 HIV-infected individuals, and 96% had a CD4 count of ≤500 cells/mm3. Correlation between the counts in individuals was poor (Spearman rank correlation r=0.5). No absolute lymphocyte count could be determined in this population as a suitable surrogate for a CD4 count of either 350 cells/mm3 or 500 cells/mm3. The currently used absolute lymphocyte count of ≤2300 cells/μL had a positive predictive value of 87% but a negative predictive value of only 17% for a CD4 of ≤350 cells/mm3 and if used as a surrogate for a CD4 of ≤500 cells/mm3 it would result in all HIV-infected individuals receiving ART including those not yet eligible. Weight, CD4 count, and absolute lymphocyte count increased significantly at 3 months following ART initiation. Conclusions. Our findings do not support the use of absolute lymphocyte count to determine antiretroviral therapy initiation in Fiji.